Orang Asli Customary Land And Adat Perpatih: A Case Study On Temuan Land In Negeri Sembilan - Izawati Wook; Arif Fahmi Md Yusof; Intan Nadia Ghulam Khan; Kamilah Wati Mohd; Fareed Bin Mohd Hassan; Abd. Hakim Bin Mohad @ Mohamad Ramli (Faculty Of Law Universiti Malaya, 2024)
Indexed by ERA/MYCITE